Developing and validating a dynamic mathematical model of a three-evaporator air conditioning (TEAC) system. (5th May 2016) - Yan, Huaxia; Deng, Shiming; Chan, Mingyin
Highlights: A physics-based dynamic model of a three-evaporator air conditioning (TEAC) system was developed. The model was experimentally validated, with an acceptable modeling accuracy. It can help develop TEAC system controllers for improved indoor humidity. It can also help study a TEAC system's operational characteristics. Abstract: The development of a physics-based dynamic model of a three-evaporator air conditioning (TEAC) system is reported. The TEAC model was built on sub-models of major system components in the TEAC system, including a compressor, an air-cooled condenser, three electronic expansion valves, three indoor units and indoor spaces. Unlike all other reported TEAC models, the TEAC model developed specifically took into account both sensible and latent heat balances on the airside of all indoor units. The TEAC model was validated using a purpose-built TEAC experimental rig. Model predictions were found to be within ±6% of the measured values, suggesting that the model developed was capable of simulating both steady state and dynamic operation of a TEAC system with an acceptable modeling accuracy. Therefore, the TEAC model developed is expected to be very useful in studying the operating performances and developing novel controllers for TEAC systems, in particular the improved indoor relative humidity control using a TEAC system.